Purpurogallin Protects Keratinocytes from Damage and Apoptosis Induced by Ultraviolet B Radiation and Particulate Matter 2.5 - Zhen, Ao Xuan; Piao, Mei Jing; Hyun, Yu Jae; Kang, Kyoung Ah; Ryu, Yea Seong; Cho, Suk Ju; Kang, Hee Kyoung; Koh, Young Sang; Ahn, Mee Jung; Kim, Tae Hoon; Hyun, Jin Won (Biomolecules & therapeutics, 2019)
Purpurogallin, a natural phenol obtained from oak nutgalls, has been shown to possess antioxidant, anticancer, and anti-inflammatory effects. Recently, in addition to ultraviolet B (UVB) radiation that induces cell apoptosis via oxidative stress, particulate matter 2.5 (PM ) was shown to trigger excessive production of reactive oxygen species. In this study, we observed that UVB radiation and PM severely damaged human HaCaT keratinocytes, disrupting cellular DNA, lipids, and proteins and causing mitochondrial depolarization. Purpurogallin protected HaCaT cells from apoptosis induced by UVB radiation and/or PM . Furthermore, purpurogallin effectively modulates the pro-apoptotic and anti-apoptotic proteins under UVB irradiation via caspase signaling pathways. Additionally, purpurogallin reduced apoptosis via MAPK signaling pathways, as demonstrated using MAPK-p38, ERK, and JNK inhibitors. These results indicate that purpurogallin possesses antioxidant effects and protects cells from damage and apoptosis induced by UVB radiation and PM .